Zumba Exercise Training in the Management of Body Composition and Insulin Resistance in Sedentary Obese Women - Alhajri, Ahlam Saleh (Journal of Ecohumanism, 2024)
Obesity is a pathophysiologic component of type 2 diabetes (T2D) and is typically linked to insulin resistance (IR). However, incorporating regular physical exercise into one’s daily schedule is an effective approach to managing IR, blood sugar levels, and general health. The study’s goal is to assess the feasibility of the Zumba fitness program and its effects on body composition and IR indicators. It is a quasi-experimental design for a single-group pre- and post-Zumba dancing intervention at a fitness center in Al-Ahsa Governorate, Saudi Arabia. Sixty-two sedentary obese women (body mass index [BMI]: 37.55 ± 3.99 kg/m2) 32.5± 0.56 years, completed a 16-week intervention attending moderate to vigorous Zumba dancing sessions 5 d/week, 60 min/class. Study instruments were structured by anthropometric measurements, body composition analysis, and some biochemical markers. After implementing the Zumba exercise program, the results show a substantial improvement in BMI, body fat composition, and IR when compared to before the program. According to body fat position, the reduction in fat composition ranged from 3.7 to 9.71%, while BMI decreased on average by around 6.31%. Significant variations have also been noted in fasting blood glucose levels of 28.04%, in leptin levels of 13.75%, in insulin levels of 28.27%, and IR levels of 8.83%. Further, decrease in total cholesterol, triglycerides, very-low-density lipoprotein cholesterol, and low-density lipoprotein cholesterol were between 2.18% and 4.91%, and the increase in high-density lipoprotein was 5.22%. Total bilirubin, total protein, and total albumin did not vary significantly between the pre- and post-program periods, though aspartate aminotransferase, alkaline transaminase, and alkaline phosphatase did. In conclusion, the program demonstrated strong feasibility and adherence, and it had a favorable impact on body weight, BMI, body fat composition, lipid profiles, and IR parameters, which can improve insulin sensitivity and stop women from developing T2D in the future.